Nurse as educator : principles of teaching and learning for nursing practice - Bastable, Susan B. (Burlington, MA : Jone and Bartlett Learning, 2023)
Nurse as Educator: Principles of Teaching and Learning for Nursing Practice, Sixth Edition prepares nurse educators, clinical nurse specialists, and nurse practitioners and students for their ever-increasing role in patient teaching, health education, and health promotion. One of the most outstanding and unique features of this text is that it focuses on multiple audiences therefore making it applicable to both undergraduate and graduate nursing courses. The Sixth Edition features coverage of relevant topics in nursing education and health promotion such as health literacy, teaching people with disabilities, the impact of gender and socioeconomics on learning, technology for teaching and learning, and the ethical, legal, and economic foundations of the educational process
Part One. Perspective on Teaching and Learning -- Part Two. Characteristics of the Learner -- Part Three. Techniques and strategies for teaching and learning.
Includes index.
Keywords: HEALTH EDUCATION